Formulation and Evaluation of Novel Additive-Free Spray-Dried Triamcinolone Acetonide Microspheres for Pulmonary Delivery: A Pharmacokinetic Study - Mohammed Amran; El-Sayed Khafagy; Hatem I. Mokhtar; Sawsan A. Zaitone; Yasser M. Moustafa; Shadeed Gad (MDPI AG, 2022)
This work aimed to establish a simple method to produce additive-free triamcinolone acetonide (TAA) microspheres suitable for pulmonary delivery, and therefore more simple manufacturing steps will be warranted. The spray-drying process involved the optimization of the TAA feed ratio in a concentration range of 1-3% w/v from different ethanol/water compositions with/without adding ammonium bicarbonate as a blowing agent. Characterization of the formulas was performed via scanning electron microscopy, Fourier-transform infrared spectroscopy, differential scanning calorimetry, and powder X-ray diffraction. Our results indicated that the size and morphology of spray-dried TAA particles were dependent on the feed and solvent concentrations in the spray-dried formulations. Furthermore, adding the blowing agent, ammonium bicarbonate, did not produce a significant enhancement in particle characteristics. We prepared additive-free TAA microspheres and found that TAA formulation #1 had optimal physical properties in terms of diameter (2.24 ± 0.27 µm), bulk density (0.95 ± 0.05), tapped density (1.18 ± 0.07), and flowability for deposition during the pulmonary tract, from a centric airway to the alveoli as indicated by Carr's index = 19 ± 0.01. Hence, formulation #1 was selected to be tested for pharmacokinetic characters. Rats received pulmonary doses of TAA formula #1 and then the TTA concentration in plasma, fluid broncho-alveolar lavage, and lung tissues was determined by HPLC. The TAA concentration at 15 min was 0.55 ± 0.02 µg/mL in plasma, 16.74 ± 2 µg/mL in bronchoalveolar lavage, and 8.96 ± 0.65 µg/mL in lung homogenates, while at the 24 h time point, the TAA concentration was 0.03 ± 0.02 µg/mL in plasma, 1.48 ± 0.27 µg/mL in bronchoalveolar lavage, and 3.79 ± 0.33 µg/mL in lung homogenates. We found that TAA remained in curative concentrations in the rat lung tissues for at least 24 h after pulmonary administration. Therefore, we can conclude that additive-free spray-dried TAA microspheres were promising for treating lung diseases. The current novel preparation technology has applications in the design of preparations for TAA or other therapeutic agents designed for pulmonary delivery.